2000
DOI: 10.1111/j.8755-8920.2000.430102.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐1 Levels in the Supernatant of Conditioned Media of Embryos Grown in Autologous Endometrial Coculture: Correlation with Outcome After In Vitro Fertilization

Abstract: We have demonstrated a significant improvement in blastomere number and frag with ECC. The presence of IL-1beta in the CM was negatively associated with embryonic development and clinical pregnancy. The presence of IL-1alpha in the CM was negatively associated with embryonic development and the presence of IL-1ra in the CM was positively associated with embryonic development. Whether IL-1beta itself interferes with successful outcome after embryo transfer or if it is a marker for undetected endometritis in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 11 publications
2
16
0
1
Order By: Relevance
“…We have also previously demonstrated the importance of IL-1 production by endometrial cells in IVF when utilizing autologous endometrial coculture (8). We have shown that the IL-1 cytokines are elaborated in our autologous endometrial coculture system.…”
Section: Discussionmentioning
confidence: 68%
“…We have also previously demonstrated the importance of IL-1 production by endometrial cells in IVF when utilizing autologous endometrial coculture (8). We have shown that the IL-1 cytokines are elaborated in our autologous endometrial coculture system.…”
Section: Discussionmentioning
confidence: 68%
“…Moreover, IL-1b secreted by the human embryo may act as signal to the endometrium (De los Santos et al 1996, Krussel et al 2003. Indeed, high concentrations of IL-1b in the culture media of human embryos have been correlated with successful implantation after in vitro fertilisation (Sheth et al 1991, Barañ ao et al 1992, Spandorfer et al 2000. A critical role in early implantation is also suggested by the fact that IL-1ra blocks the response of the endometrium to human chorionic gonadotrophin (hCG) from the pre-implantation in the baboon (Strakova et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The development of such kind of embryo-supportive tеchniques based on the surrounding feeder cells represents just one of the various strategies for improving the suboptimal conditions provided by the artificial media for in vitro embryo culture. The main idea behind co-culture as a concept is that the supportive cells exert their beneficial effect by enhancing the in vitro conditions through detoxification of the culture medium and removal of potentially noxious agents such as heavy metals and free radicals and by providing the necessary signals (via cell-to-cell interactions) or/and release of a broad spectrum of embryotrophic factors (e.g., growth factors; cytokines; nutrients) [3][4][5][6]. The final result should be mimicking the optimal physiological conditions of the maternal environment within the uterine cavity and by reproducing the intimate in vivo cross-communication links between the embryo and the cells of the receptive endometrium.…”
Section: Introductionmentioning
confidence: 99%
“…To date, a wide variety of co-culture systems have been reported to have favorable effects on preimplantation embryo development such as improved growth [3,5,[7][8][9], morphological characteristics [10], and blastocyst development [11]; decreased incidence of fragmentation [3,5,12] and apoptosis [13]; and higher pregnancy [4,10] and delivery rates [14]. Among the broad range of somatic cell lines with welldetermined embryotrophic properties, Vero cells [15][16][17][18], cumulus-granulosa cells [19][20][21][22][23], and endometrial cells from the lining of the uterus [3-5, 11, 12, 24, 25] could be defined as the most popular and commonly used in clinical in vitro fertilization programs.…”
Section: Introductionmentioning
confidence: 99%